Transmission of Environmental Knowledge and Land Skills among Inuit Men in Ulukhaktok, Northwest Territories, Canada and Adaptation to Climate Change - Pearce, T; Ford, J; Furgal, C (2011)
This paper investigates the relationship between the transmission of environmental knowledge and land skills, and human adaptation to climate change. This relationship is empirically tested in an arctic community to document how environmental knowledge and land skills are transmitted among Inuit and what role, if any, do environmental knowledge and land skills play in adaptation to climate change. The transmission of environmental knowledge and land skills was studied with Inuit men in Ulukhaktok, Northwest Territories, Canada. Just over half of all skills were being transmitted through ‗hands-on‘ learning among younger respondents. Some skills including general hunting, traveling, fishing and camp-related skills, and skills related to caribou, musk ox, seal (summer) and duck hunting were transmitted well. Others such as fur preparation, dog team handling, winter seal hunting, traveling on the sea ice, and some traditional navigation and weather forecasting skills, were not. Despite similar learning ages between generations, there has been an incomplete transmission of several skills among younger respondents. In the context of adaptation to climate change, incomplete skill transmission is of particular concern. For example, most young respondents had not learned the detailed knowledge needed to navigate in poor visibility, how to anticipate and cope with changes in weather, or how to travel on the sea ice in different seasonal conditions. Based on these findings, a number of insights are provided for supporting skills transmission in the context of adaptation planning for climate change.